The influences of product quality, price and service quality to increase consumer satisfaction of Dorayaki product at CV Abe Seika - Sarah Isniah; Romli Septiadi; Aprillia Susmita (Universitas Mercu Buana, 2020)
Business is a trade undertaken by group organized in order to make a profit by producing and selling goods and services to meet the community needs. Business is not only seen from the clothing business but other like food or beverage business that encompasses the entire world. In this modern business era, more and more emerging SMEs make competition tighter. By examining the influence of product quality, price, it is and service quality variables that expected in this research strategy output can increase consumer satisfaction of Dorayaki products at CV Abe Seika. The survey method with a quantitative approach was used in this study.The questionnaire results were processed using SEM (structural equation modeling). From the study results known that produced a strategy of product quality variables with Dorayaki product quality indicators. It is expected to increase customer satisfaction from implementing results the right strategy. Therapy needs further research on success of this consumer satisfaction assessment.